Organizational Restructuring Of Regional Apparatuses Of Denpasar Municipal Government To Achieve Bureaucratic Reform - Subanda, I Nyoman; Prabawati, Ni Putu Anik (UI Scholars Hub, 2018)
The determination of Grand Design of Bureaucratic Reform is the first measure for local government to reform local bureaucracy. There are eight areas of change that become the priority agenda in implementing bureaucratic reform. One of them is organizational restructuring. This study aims to determine the form of organizational restructuring carried out by the Government of Denpasar to achieve bureaucratic reform in Denpasar. The method applied in this research is qualitative descriptive method. The data collection is carried out through interview, observation, and literature study. The analysis applies qualitative descriptive analysis. The findings show that the Government of Denpasar has carried out bureaucratic reform in accordance with the Presidential Regulation No. 81 of 2010 on the Grand Design of Bureaucratic Reform with priority agenda of eight areas of change. The implementation of organizational restructuring in the Government of Denpasar is in accordance with applicable laws and regulations. The measures of restructuring carried out by the government of Denpasar are delayering, reorganizing and competency measurement. The supporting factors for the implementation of the restructuring in the Government of Denpasar are regulations and human resources, while the inhibiting factors are the issuance time of the regulation and the placement of human resources.